TINGKAT EFEKTIVITAS PEMBANGUNAN RUSUNAWA BAGI PENGHUNINYA - Munandar, Charis (Geo-Image, 2016)
The purpose of this study were to; 1) Knowing the level of development effectiveness Rusunawa Kraton for the residents. 2) Knowing contribution Rusunawa Kraton development for low income people. This research method using random sampling method. The study population are all residents Rusunawa Kraton. Variable research is a means, and utility construction prasanara Rusunawa Kraton. Data collection techniques include observation, documentation, and interviews with questionnaires. Data were analyzed using quantitative descriptive analysis. The results showed that the level of effectiveness of the construction of high-rise apartments have been very effective for low-income communities, community participation bedampak Tegal were positive in the construction of the palace Rusunawa Kraton.